Acute stress response of Kootenai River white sturgeon Acipenser transmontanus Richardson reflected in peritoneal fluid and blood plasma - M. D. Zuccarelli; M. Kusakabe; I. Nakamura; E. F. Prentice; G. Young; R. L. Ingermann (Journal of Fish Biology, 2008)
To evaluate whether stress‐response indicators in blood plasma (BP) are similarly reflected in the peritoneal fluid (PF) white sturgeon Acipenser transmontanus were stressed by a 30 min air exposure and pH, PCO 2 , osmolality, cortisol, glucose and lactate levels measured. Changes in certain stress indicators in the BP (pH, PCO 2 , osmolality and glucose) also occurred in the PF, while stressor‐induced changes in cortisol and lactate were restricted to the BP. Data suggest that PF is a modified ultrafiltrate of the blood and potentially a useful indicator of animal stress.